National Parks and Indigenous Land Management. Reshaping Tourism in Africa, Australia and Canada - LeBlanc, Julie; LeBlanc, Vivianne (Ethnologies, 2010)
Tourists make decisions that impact the places they visit. Through an economic and development perspective, tourism has grown into a capital venture for most countries all while having the challenging task of operating under specific policies that shape visiting experiences. These experiences are critical in assessing how, by and for whom land is developed and managed. This article explores three continents as case studies: Eastern Africa's Maasai Mara, Australia's Uluru-Kata Tuta site and the Torngat Mountains National Reserve Park in Canada. The African and Australian examples are based on participant-observation fieldwork by the authors while the Torngat Mountains serves as an example of what could become the new National Reserve Park in Canada and its possible tourism impact forecasting. Critical analysis is particularly important in this article as we examine, compare and contrast the development approach and land management policies from the tourist's experiential perspective. The purpose of this article is to illustrate the various levels and politics of planning involved in the recognition, nationalization and touristification of heritage sites as well as the creation of identities based on local confines. More specifically, with the focus on tourist experience, we attempt to uncover the nature of theory and practice in indigenous, private and public land management for tourism exploitation.